Effects of Carbohydrate-Based and Protein-Carbohydrate Rations on Wild Bobwhite Nesting and Harvest Demographics - Andrew N. Tri; Fidel Hernandez; David G. Hewitt; William P. Kuvlesky Jr.; Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) reproduction is a nutrient-intensive process. Arthropods are essential for breeding bobwhite hens and their offspring. Traditional supplemental feeding programs use corn and milo and typically neglect the protein needs of bobwhites. Commercial bobwhite rations are widely available but are seldom used in feeding programs due to high cost and lack of an appropriate supplement for field use. We compared the effect of a protein-carbohydrate ration (PC) to the effects of a carbohydrate only ration (CO) on: (1) bobwhite hen nesting demographics (clutch size, ordinal clutch initiation date, Mayfield nest survival), and (2) fall relative abundance (coveys moved/hr hunting). Nesting parameters for bobwhites based on a sample of 60 hens during the 2008 breeding season in South Texas were statistically similar based on overlap of 95% confidence intervals for both the PC and CO supplements. Mayfield nest success was high for both the PC ration (75.2%) and the CO ration (73.1%). Coveys moved during hunting (4.17 6 14 coveys/hr in pastures with CO feed and 4.2 6 12.5 coveys/hr in pastures with PC feed) did not differ during the 2008–2009 hunting season. The 2009 nesting season was a failure because all study animals died due to drought. Weekly Kaplan-Meier survival estimates of bobwhite hens were 6 times higher in 2008 than in 2009. The PC ration in our study provided no benefit to bobwhite populations or enhancement of wild bobwhite reproductive parameters over the CO ration. The additional cost of using PC over CO is not justified based on our results.
Keywords: Colinus virginianus; hens; nest success; northern bobwhite; protein; supplemental feed